Effect of Hallux Valgus Deformity on Gait Phases and Lower Limb Joints Angular Displacement in Old Female During Gait: Evaluation of Gait Kinematics in lower limb of Hallux Valgus Elderly Women - Sardary, Samane; Tabatabai, Farhad; Noruzy, Hamid reza; Fatahi, Ali (Journal of Clinical Physiotherapy Research, 2022)
Abstract Back ground and objective: Hallux valgus is a common lower extremity deformity especially in older women that affects balance and increases falling risk among them. How this deformity kinematically effects balance has not thoroughly investigated. So, we want to know if there are differences in gait phases and angular displacement between healthy and hallux valgus elderly women during gait as an independence and health vital factor in elderly adults. Materials & Methods: Participants in this study were 12 (54.25±2.76 years old) healthy and 12 (54.5±3.25 years old) hallux valgus women. To evaluate the gait phases (percent) and angular displacement (degree) we use a localized Motion Capture System by IMU-based to measure kinematics of motion. All modules were defined and fastened about right hip, shank and foot. Results: The results showed that ankle joint angular displacement was significantly different in all planes (frontal: 45%, horizontal:95%, sagittal: 40% of gait cycle)), whereas angular displacement was significantly different just in sagittal plane of knee joint (44% of gait cycle) and sagittal and frontal planes of hip (10 & 8% of gait cycle). Conclusion: Ankle more adduction, toe out and greater knee flexion and increasing hip abduction and extension at the late swing phase in hallux valgus elderly group probably indicate that they avoid from completely transfer body weight in to forefoot during toe off and tent to transfer the body weight in to lateral component of the foot during stance phase of gait.